2022
DOI: 10.1080/10717544.2022.2072412
|View full text |Cite
|
Sign up to set email alerts
|

Optimized 2-methoxyestradiol invasomes fortified with apamin: a promising approach for suppression of A549 lung cancer cells

Abstract: Certain anticancer agents selectively target the nucleus of cancer cells. One such drug is 2-methoxyestradiol (2ME), which is used for treating lung cancer. To improve the therapeutic effectiveness of these agents, many new methods have been devised. 2ME was entrapped into the core of hydrophobic invasomes (INVA) covered with Phospholipon 90G and apamin (APA). The Box–Behnken statistical design was implemented to enhance the composition. Using Design-Expert software (Stat-Ease Inc., Minneapolis, MN), the INVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Accordingly, emulsomes were chosen for investigation in this work. In addition, apamin was used for surface-functionalization of the optimized mulsomal formulation to provide additional advantage of enhancing uptake of EGA by cancerous cells [ 35 ]. It is worth noting that the reported cytotoxic activity of bee venom components including apamin could also augment the cytotoxicity of EGA [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, emulsomes were chosen for investigation in this work. In addition, apamin was used for surface-functionalization of the optimized mulsomal formulation to provide additional advantage of enhancing uptake of EGA by cancerous cells [ 35 ]. It is worth noting that the reported cytotoxic activity of bee venom components including apamin could also augment the cytotoxicity of EGA [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…12 In the past decades, 2ME2 has been considered to be a potential cancer chemotherapeutic agent that is capable of inhibiting cell growth and inducing cell death in malignant cell lines such as colon carcinomas, melanoma, and the lungs. [13][14][15] In recent studies, researchers have found other antitumor mechanisms of 2ME2. Lu's study demonstrated that 2ME2 could inhibit the expression of HIF-1α and confer radiosensitivity in ECA-109 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is then followed by a conjugation reaction of the enzyme catechol‐O‐methyltransferase generating 2ME2 from 2‐hydroxyestradiol 12 . In the past decades, 2ME2 has been considered to be a potential cancer chemotherapeutic agent that is capable of inhibiting cell growth and inducing cell death in malignant cell lines such as colon carcinomas, melanoma, and the lungs 13–15 . In recent studies, researchers have found other antitumor mechanisms of 2ME2.…”
Section: Discussionmentioning
confidence: 99%
“…However, the therapeutic applications of 2ME are constrained due to its poor solubility which negatively affects its bioavailability and tissue distribution [ 58 , 59 ]. In this regard, loading of 2ME in nanoparticles has been shown to improve its pharmacokinetic and pharmacodynamics characteristics [ 60 , 61 , 62 ]. Thus, this study aimed at evaluating the potential of 2ME loaded TPGS micelles to prevent CSA-induced nephrotoxicity in rats.…”
Section: Discussionmentioning
confidence: 99%